The Legal Isomorphism in Indonesian Constitutional Amendment: Interplay Between Foreign Influence and National Identity - Azhari, Aidul Fitriciada; Rizka, Rizka; Setiawati, Diana; Almira, Sekar Diah Ayu; Salmande, Ali (Unissula, 2025)
The post-authoritarian reform era in Indonesia (starting in 1998) was characterized by a push to democratize the state system, leading to the adoption of several foreign, democratic, or